On the right commutativity of loop rings - Vasantha Kandasamy, W. B. (Universidad de Costa Rica, 2011)
Its proved that extra loops and central loops are conjugated closed, consequently  they are G-loops. It is also proved that extra loops and central loops are M-loops.